Analisis Pengaruh Pelaksanaan Evaluasi Terhadap Kualitas Pembelajaran Di Sekolah Dasar - Romasda Limbong; Renti Semina Sinaga; Syahrial (CV. ITTC INDONESIA, 2024)
Evaluation is a step of the teacher in mapping the learning results of the pupils and performing improvements in teaching to improve the quality of learning. The purpose of this research is to exhibit the impact of evaluation on the quality of learning in primary schools. This research is qualitative research that is a library study by searching for reliable sources either in written form or in a relevant digital format without a direct drop in popularity. Based on the analysis of library studies of several scientific articles, it was found that the use of digital learning media can improve the achievement of elementary school students.